1990
DOI: 10.1161/01.res.66.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cytosolic free calcium, contracture, ATP, and irreversible ischemic injury in perfused rat heart.

Abstract: The relations between ATP depletion, increased cytosolic free calcium concentration [( Cai]), contracture development, and lethal myocardial ischemic injury, as evaluated by enzyme release, were examined using 19F nuclear magnetic resonance to measure [Cai] in 1,2-bis(2-amino-5-fluorophenoxy)ethane-N,N,N',N'-tetraacetic acid (5F-BAPTA)-loaded perfused rat hearts. Total ischemia at 37 degrees C was induced in beating hearts, potassium-arrested hearts, magnesium-arrested hearts, and hearts pretreated with 0.9 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
1
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(145 citation statements)
references
References 52 publications
(18 reference statements)
9
134
1
1
Order By: Relevance
“…This is accompanied by only a small temporary rise in ADP as the adenine nucleotides are degraded to nucleosides and bases [115][116][117]. There is therefore a net loss of adenine nucleotides.…”
Section: Adenine Nucleotides and P Imentioning
confidence: 99%
“…This is accompanied by only a small temporary rise in ADP as the adenine nucleotides are degraded to nucleosides and bases [115][116][117]. There is therefore a net loss of adenine nucleotides.…”
Section: Adenine Nucleotides and P Imentioning
confidence: 99%
“…Bolli and his colleagues (1988) using electron paramagnetic resonance spectroscopy detected a burst of free radical formation within the coronary venous effluent in dogs subjected to 15min of coronary occlusion and reperfusion; other studies found that production of free radicals increased markedly in isolated hearts of rabbit or rat undergoing global ischaemia and reperfusion (Zweier et al, 1987;Garlick et al, 1987; Kramer et al, 1987) and pretreatment with the oxygen radical-scavenging agents superoxide dismutase and catalase reduced the degree of left ventricular dysfunction in canine models of stunned myocardium (Gross et al, 1986;Ambrosio et al, 1987;. Nevertheless, recent studies also indicate that other factors independent of free radicals are involved in the pathogenesis of myocardial stunning such as: calcium overload (Kusuoka et al, 1987; Lee et al, 1987;Steenbergen et al, 1990;Sun & Lin, 1990), heterogeneous impairment of myocardial perfusion (Stahl et al, 1986) and neutrophil accumulation in the postischaemic myocardium (Westlin & Mullane, 1989) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in the levels of tissular ATP was followed by a significant increase in intracellular Ca +2 levels 24 . Several authors 19,25,26 suggest that the increase in the intracellular calcium is one of the major determinants of the ischemic lesion, through a calcium-dependent mechanism that activates the catabolic enzymes, leading to irreversible damage of the plasmatic membrane, and determining cellular death.…”
Section: Groupmentioning
confidence: 95%